Adaptive noise reduction of InSAR images based on a complex-valued MRF model and its application to phase unwrapping problem - ANDRIYAN BAYU SUKSMONO; HIROSE, Akira (IEEE transactions on geoscience and remote sensing, 2002)
We propose a new adaptive noise reduction method for interferometric synthetic aperture radar (InSAR) complex-amplitude images. In the proposed method, we detect residues (singular points) in the phase image as well as their neighbors at first. Normal areas that contain no residue are used for the estimation of correct pixel values at the marked residues according to the fifth-order non-causal complex-valued Markov random field (CMRF) model. The process is performed block-wise under the assumption of a locally stationary condition of statistics. Using a CMRF lattice complex-valued neural-network, the error energy defined as the squared norm of distance between signal and estimated values is minimized by LMS steepest descent algorithm. Eventually, the number of residues is decreased. An application is also presented. An InSAR image around Mt. Fuji is processed by the proposed technique and then phase-unwrapped by the branch-cut method. It is found that after the application of the proposed method, a better phase unwrapped image can be obtained successfully. (Author)